Curing kinetics of a novolac resin modified with oxidized multi-walled carbon nanotubes - Morales Arias, Juan Pablo (2017)
The influence of oxidized multi-walled carbon nanotubes (o-MWCNTs) on the curing kinetics of a novolac resin was studied by means of non-isothermal differential scanning calorimetry. Regarding the kinetics issues, the high concentration of hydroxyl groups on the o-MWCNTs slightly modified the curing reaction of the novolac resin, shifting the differential scanning calorimetry exothermic peak to higher temperatures. The effective activation energy of the curing reaction was calculated by the isoconversional Kissinger-Akahira-Sunose method and increased by the presence of o-MWCNTs with respect to neat novolac. This change was attributed to the increase of the material viscosity. In addition, thermogravimetric analysis revealed that nanocomposites samples containing 0.4 and 1.0 wt% o-MWCNTs presented increased char yield values, indicating an improvement of flame retardancy.